Associations of meaning of illness with psychosocial, clinical, and immunological characteristics in patients with Leptomeningeal metastasis - Julie G. Walker (Elsevier, 2021)
Background: Leptomeningeal metastasis (LM) creates symptoms related to both the disease within the nervous system and treatment toxicities. Biologic processes, such as inflammation and behavioral processes, such as the meaning ascribed to illness (Meaning of Illness: MoI), can impact physical and psychosocial symptoms. The aim of this study was to understand the relationships among MoI, physical and psychosocial symptoms, and inflammation in patients with LM. Methods: Thirty enrolled participants completed the MD Anderson Symptom Inventory-Brain Tumor with spine experimental symptoms added. Meaning of illness, quality of life (QoL), and depression were captured by validated instruments. Interleukin (IL)-6 and tumor necrosis factor (TNF)-α in serum and cerebrospinal fluid (CSF) were measured by ELISA. Correlations were performed to assess relationships among the variables. Results: Participants were primarily white (73%), female (63%). Median age was 54 years (34–83). Breast (50%) and lung (20%) were most common diagnosis. Higher MoI scores were associated with better QoL (p < .01) and fewer depressive symptoms (p < .01). All CSF samples contained IL-6 and all but one sample had elevated IL-6. Higher levels of IL-6 in the CSF were associated with greater symptom burden (p < .01) and interference of symptoms in daily life (p = .02) but not MoI. Conclusions: MoI was associated with QoL and depression. High levels of IL-6 in the CSF were associated with more severe symptoms. This study provides the groundwork for future research, including interventional studies to improve QoL in patients with LM.